2010
DOI: 10.1590/s1984-70332010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Yield traits as selection indices in seedling populations of cassava

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
(21 reference statements)
2
12
1
5
Order By: Relevance
“…The high genetic correlation between foliar CBSD3s and CBSD6s in the current study implies the possibility of single and effective assessment of CBSD foliar symptoms at 6 MAP, permitting more efficient use of resources. phenotypic (r p = 0.56) and genetic correlation (r g = 0.41) between HI and root weight with the large number of clones evaluated in the present study agree with the results of previous studies conducted in other breeding populations (Ojulong et al, 2010;Akinbo et al, 2012), suggesting that HI could be used as a complementary trait for RTWT to select for fresh root yield, particularly at early stages of selection, when a large number of clones are evaluated in smaller plots. phenotypic (r p = 0.56) and genetic correlation (r g = 0.41) between HI and root weight with the large number of clones evaluated in the present study agree with the results of previous studies conducted in other breeding populations (Ojulong et al, 2010;Akinbo et al, 2012), suggesting that HI could be used as a complementary trait for RTWT to select for fresh root yield, particularly at early stages of selection, when a large number of clones are evaluated in smaller plots.…”
Section: Estimates Of Phenotypic and Genetic Correlations Among Traitssupporting
confidence: 91%
“…The high genetic correlation between foliar CBSD3s and CBSD6s in the current study implies the possibility of single and effective assessment of CBSD foliar symptoms at 6 MAP, permitting more efficient use of resources. phenotypic (r p = 0.56) and genetic correlation (r g = 0.41) between HI and root weight with the large number of clones evaluated in the present study agree with the results of previous studies conducted in other breeding populations (Ojulong et al, 2010;Akinbo et al, 2012), suggesting that HI could be used as a complementary trait for RTWT to select for fresh root yield, particularly at early stages of selection, when a large number of clones are evaluated in smaller plots. phenotypic (r p = 0.56) and genetic correlation (r g = 0.41) between HI and root weight with the large number of clones evaluated in the present study agree with the results of previous studies conducted in other breeding populations (Ojulong et al, 2010;Akinbo et al, 2012), suggesting that HI could be used as a complementary trait for RTWT to select for fresh root yield, particularly at early stages of selection, when a large number of clones are evaluated in smaller plots.…”
Section: Estimates Of Phenotypic and Genetic Correlations Among Traitssupporting
confidence: 91%
“…An important aspect of this trait is that even with accessions with high shoot production, group 7 also has a high YiComRoo, evidenced by its high harvest index (average of 65.47%). Using phenotypic means, Ojulong et al (2010) also observed high amplitude for this trait (5 to 90%). Moreover, considering the high inheritability of the HI trait, as well as its correlation with fresh root production, some authors have used the HI as an indirect measure of root yield in the early breeding stages (KAWANO et al, 1998).…”
Section: Resultsmentioning
confidence: 84%
“…Recently, Ojulong et al (2010) reported averages for DMC ranging from 16.3% to 69.1%. However, these values are related to phenotypic averages of segregating populations in the early improvement stages and must; therefore, be confirmed in further trials with the greatest number of plants per plot.…”
Section: Resultsmentioning
confidence: 99%
“…1988), using the supplementary genotype and environment proposed by Duarte and Vencovsky (1999), Pacheco et al (2005), which in this study will be called genotype and ideal environment. Multivariate procedures have been studied in cassava by Kvistichal et al (2006), Carvalho et al (2008 and Ojulong et al (2010).…”
Section: Methodsmentioning
confidence: 99%